InfoPath 2013. - Jasperson, Ryan; Safari eBooks ([Place of publication not identified] : Intellezy, 2017)
"This course introduces the user to Microsoft InfoPath 2013, a tool that allows you to create forms and gather data. In this course, you will learn how to use InfoPath within SharePoint and how to create, edit, and publish a form. You will also look at working with list forms and how to properly utilize the different controls and their associated properties. This course will also review some of the more advanced features of InfoPath, such as creating and modifying a data source or working with repeating sections. Finally, you will look at how to use InfoPath forms within Sharepoint using WebParts."--Resource description page.
Title from resource description page (Safari, viewed October 17, 2017).
Presenter, Ryan Jasperson.
Keywords: Microsoft InfoPath; Microsoft SharePoint (Electronic resource); Business -- Forms -- Computer programs; Electronic books